2019
DOI: 10.1038/s41398-019-0466-x
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressants affect gut microbiota and Ruminococcus flavefaciens is able to abolish their effects on depressive-like behavior

Abstract: Accumulating evidence demonstrates that the gut microbiota affects brain function and behavior, including depressive behavior. Antidepressants are the main drugs used for treatment of depression. We hypothesized that antidepressant treatment could modify gut microbiota which can partially mediate their antidepressant effects. Mice were chronically treated with one of five antidepressants (fluoxetine, escitalopram, venlafaxine, duloxetine or desipramine), and gut microbiota was analyzed, using 16s rRNA gene seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
155
2
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(171 citation statements)
references
References 97 publications
8
155
2
6
Order By: Relevance
“…To identify the microbial biomarkers that most accurately reflect the underlying pathology of MDD and BD, and because emerging studies have shown that gut microbial composition may be influenced by antidepressants and antipsychotics, only well‐matched unmedicated subjects were recruited in the discovery set. In the validation set, to better confirm the diagnostic generalizability of our differential diagnostic assay in a closer‐to‐real‐world scenario, the samples were not matched on age and gender.…”
Section: Discussionmentioning
confidence: 99%
“…To identify the microbial biomarkers that most accurately reflect the underlying pathology of MDD and BD, and because emerging studies have shown that gut microbial composition may be influenced by antidepressants and antipsychotics, only well‐matched unmedicated subjects were recruited in the discovery set. In the validation set, to better confirm the diagnostic generalizability of our differential diagnostic assay in a closer‐to‐real‐world scenario, the samples were not matched on age and gender.…”
Section: Discussionmentioning
confidence: 99%
“…16,22,23 Moreover, recent experiments showed that FLX alters the gut microbiota in rats, 24,27 and in mice. 25,26,28,29 Interestingly, the specific bacteria underlying this difference do not match between studies (Table 1). Whereas we found significant increases in Prevotella and Ruminococcus relative abundance during pregnancy and lactation in FLX-treated rats, Cussotto et al report a complete depletion of some Prevotella OTUs in FLX-treated male rats, 24 and Lukić et al found many Ruminococcaceae OTUs to be lower in FLX-and escitalopram-treated mice relative to controls.…”
Section: Discussionmentioning
confidence: 99%
“…9 Several studies have found alterations in the gut microbiota composition of patients with major depression [10][11][12][13][14][15][16] and rodents with depressive-like symptoms. [17][18][19][20][21] Moreover, recent human population-based studies, 16,22,23 as well as rodent experiments, [24][25][26][27][28][29] showed that SSRIs modulate the gut microbiota composition, an effect that may be related to their in vitro antimicrobial properties. 24,30,31 The gut microbiota synthesizes a variety of metabolites that reach the systemic circulation, 32,33 which is of special relevance during pregnancy and lactation when there is a high metabolic demand.…”
Section: Introductionmentioning
confidence: 99%
“…Minerbi's group [27] also collected information regarding drug use and smoking status, but little attention was given to these as confounders, nor was detail regarding the type, or extent of drug use or smoking provided. Drugs of many kinds may impact gut bacteria and their metabolism, and vice-versa: smoking is associated with an altered gut microbial profile [48] and the Ruminococcus genus (which was overexpressed in Clos-Garcia's patient group) can impact antidepressant metabolism, drugs which also alter the gut microbiota [49].…”
Section: Gut Microbiotamentioning
confidence: 99%